GAMBARAN KEBUTUHAN CAIRAN DAN ELEKTROLIT PADA PEMBEDAHAN NEFROTOMI: NARRATIVE REVIEW - Made Suandika; Ceria Febriyani; Rahmaya Nova Handayani; Ayu Wardani; Anisa Dwiyanti Djafar (Poltekkes Kemenkes Bengkulu, 2025)
ABSTRAK Nephrotomy procedures, whether elective such as Percutaneous Nephrolithotomy (PCNL) or emergency due to renal trauma, carry a significant risk of disrupting fluid and electrolyte homeostasis. Perioperative fluid imbalance increases the risk of complications including hypovolemia, hypervolemia, electrolyte disturbances (hyperkalemia, hyponatremia), metabolic acidosis, and Acute Kidney Injury (AKI), particularly in patients with Chronic Kidney Disease (CKD). This narrative review aims to analyze perioperative fluid management requirements in nephrotomy surgery based on recent scientific literature. Articles were identified through Google Scholar and PubMed, with 15 publications from 2011–2024 selected based on relevance to perioperative fluid therapy and nephrotomy. The synthesis indicates that optimal fluid strategies include preoperative hydration optimization through Enhanced Recovery After Surgery (ERAS) protocols, intraoperative hemodynamic-based fluid therapy such as Perioperative Goal-Directed Therapy (PGDT), preference of balanced crystalloid solutions (Lactated Ringer/Acetated Ringer) to prevent hyperchloremic metabolic acidosis, and strict postoperative fluid monitoring to prevent fluid overload, especially in CKD patients with CRRT indication. In conclusion, perioperative fluid management in nephrotomy must be individualized, carefully monitored, and evidence-based to prevent postoperative renal complications and improve patient outcomes.